Urban Air Mobility as the Environmental-Friendly Transport of the future in Indonesia? Some Legal Considerations - van Huis Stijn Cornelis (E3S Web of Conferences, 2023)
This paper investigates the legal framework required to develop a safe and sustainable Urban Air Mobility system in Indonesia. A coherent and comprehensive legal framework for UAM minimizes the risks posed by mass application of drones. Risk mitigation is essential, as public opinion, social resistance, and costs will determine how the public will receive such services. To ensure sustainability, drone services must be safe, comfortable, and not disturb local communities too much. Accidents are detrimental to trust and increase insurance costs. Areas that require special regulatory attention are requirements for aircraft, requirements for the ground station, requirements for operations, minimization of visual and sound pollution, and rights and responsibilities of operators vis-à-vis users and third parties. This paper explores the extent to which current Indonesia’s drone regulations provide a legal framework for future mass use of drones for transportation and provide recommendations for further regulation and risk mitigation.